2014
DOI: 10.1088/0963-0252/23/4/045013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diffusion and non-local radiation transport on the laser amplification of a He–Ne ring laser gyro

Abstract: The influence of the transport of excited atoms on the laser amplification inside the positive column of a low-pressure He-Ne dc discharge of a ring laser gyro has been studied. Both non-radiative diffusion and the contribution of radiation transport have been considered. The transport induced by the radiation trapping has been determined using a Monte-Carlo simulation, taking into account an isotopic structure for the neon and the collisional line broadening in presence of helium. The transfer matrix for spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…J S Macé et al established a model of He-Ne plasma discharge and investigated the density distribution of excited state atoms in the anode column of the DC discharge. They found that both radiative and non-radiative diffusion of excited state atoms significantly affect the radial distribution of gain for laser modes [21]. However, the plasma dynamics and atomic state distribution under different He/Ne gas ratios conditions have seldom been studied.…”
Section: Introductionmentioning
confidence: 99%
“…J S Macé et al established a model of He-Ne plasma discharge and investigated the density distribution of excited state atoms in the anode column of the DC discharge. They found that both radiative and non-radiative diffusion of excited state atoms significantly affect the radial distribution of gain for laser modes [21]. However, the plasma dynamics and atomic state distribution under different He/Ne gas ratios conditions have seldom been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, two main classes of solution approaches are used. The first is based on Monte-Carlo methods [15][16][17][18][19][20][21][22][23][24][25][26]. The Monte-Carlo technique allows for the consideration of complex geometries and inhomogeneous distributions of absorbing atoms, as well as including the effects of partial frequency redistribution.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling constants were first introduced in [36] and they describe a probability that two arbitrary volume elements (cells) in plasma are connected due to the emission and absorption of a photon and account for the nonlocal photo-pumping of one plasma cell by another. The influence of the radiation transport on the laser amplification in the positive column of a low-pressure He-Ne DC discharge of a ring laser gyro has been studied in paper [39]. Review [40] describes the main features of the transport mechanisms of particles through the collisional diffusion and photons due to the radiation trapping in various problems of gas discharge physics.…”
Section: Introductionmentioning
confidence: 99%